2011
DOI: 10.1002/jbm.a.33142
|View full text |Cite
|
Sign up to set email alerts
|

Regulation on the biocompatibility of bioactive titanium metals by type I collagen

Abstract: To study the regulation on the biocompatibility of titanium metal surface structure, the interaction between the collagen and the titanium surface structure were studied with titanium surfaces subjected to anodic oxidation and acid-alkali treatment. The cell response on the treated surfaces was studied in vitro experiments of MG63 osteoblasts. The effects of different collagen adsorption ability on the biomineralization were investigated with simulated body fluid (SBF) experiment and osteoblasts culture experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 27 publications
(24 reference statements)
0
14
0
Order By: Relevance
“…Biomedical titanium has been made into bone devices such as bone plates, bone screws and artificial hip joint for many years . After implanted in vivo , the similar interaction between surface modified titanium and the rhBMP‐2 protein takes place adjacent to the host bone, which greatly influences the new bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…Biomedical titanium has been made into bone devices such as bone plates, bone screws and artificial hip joint for many years . After implanted in vivo , the similar interaction between surface modified titanium and the rhBMP‐2 protein takes place adjacent to the host bone, which greatly influences the new bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…Type I collagen, one of the main components of bone extracellular matrix, is an intriguing candidate for surface immobilization because it can modulate various aspects of cell behaviors, such as controlling cell migration and attachment by interacting integrin located on cell membrane . Early reports have shown that type I collagen immobilized on Ti‐based implants can modulate various aspects of cell behavior . It can be hypothesized that the biological function of titanium coating would also be improved by immobilizing type I collagen.…”
Section: Introductionmentioning
confidence: 99%
“…In adsorptive immobilization, collagen is physically adsorbed on the surface through van der Waals, hydrophobic or electrostatic forces . The surface characteristics of Ti‐based implants, such as the wettability, electric charge, and hydrophilicity, influence the absorption of collagen . In covalent immobilization, collagen can be covalently bound onto titanium surfaces using a variety of cross‐linking agents, such as aminopropylsilane, glutaraldehyde or carbodiimide .…”
Section: Introductionmentioning
confidence: 99%
“…Xia et al 11 obtained HA/COL composite coating by co-precipitation of type I collagen and apatite in a collagen-containing modified simulated body fluid, proving that addition of collagen promoted osteoblast activity, which can lead to early bone formation. Wang et al 12 directly absorbed collagen onto the titanium surface after alkali heat treatment, then immersed it in the simulated body fluid to deposit phosphorite. It turned out that collagen addition improved the biocompatibility of the titanium substrate surface and promoted cell activity.…”
Section: Introductionmentioning
confidence: 99%